Rancang Bangun Aplikasi Bursa Kerja Sebagai Pendukung Seleksi Awal Calon Pelamar Berbasis Web (Studi Kasus PT Jawa Pos Koran) - Frastyawan, Nyoman; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Jawa Pos is one of the print media in the form of a newspaper that has long published in Surabaya. Revenue earned from the Jawa Pos newspaper sourced on the sale of newspapers and from the number of ads that are loaded, including the job advertisements. As a print media company that is growing rapidly, Jawa Pos extremely utilize information technology and communications, both hardware and software.In general, an online job fair there must be new jobs, new jobs lists provided by the labor provider. Log in, used to log into the application, whether job seekers or job providers. Administrators, contains the information required by the manager of the online job exchange website.By looking at the opportunities that exist, then the Jawa Pos requires a system that is able to provide information that could increase its advertising revenue and business opportunities in the online world. Until now there have been several sites the labor market, among others, is jobsdb.com, duniakarir.com, and jobloker.co.id. Where the online job market is still using a search based on criteria not support the request and Job Applicants selection process. So Jawa Pos wants to create a job market that is superior compared to other job market, Job Fair advantages owned by Jawa Pos is going to be supported by the selection Job Applicants.Keyword: Labor, Applicants, Opportunities, Application